(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the problem of what came to be named in the field of the methodology of the Islamic Law as “sharu man kablana” (the Law of the pre-Islamic nations or religions). This set of laws is an additional one to other law mechanisms of the Islamic Sharia, but, nevertheless, widely resorted to by many Islamic scholars whilst working out religious rulings. This kind of rulings, in spite of being mentioned in Koran and Sunna, were left unelaborated as far as their being or not being in force is concerned. In the course of time, this fact has driven some scholars into inferring a number of theoretical and practical conclusions, some of which are dealt with in the article. Keywords: Islamic law, law methodology, The Law of the pre-Islamic nations or religions, religious proofs, monotheism.